Emotion Regulation and Emotional Intelligence As Predictors Of Mindful Teaching In Inclusive Pre-School Teachers - Alucyana, Alucyana; Rahma; Dian Tri Utami; Raihana; Restu Nabila (Universitas PGRI Yogyakarta, 2025)
Inclusive education is a central issue in global education reform. An element of education is the teacher. The complex role of teachers makes them vulnerable to burnout. This condition requires good emotional regulation and emotional intelligence to facilitate mindful teaching. This study aims to explore how emotion regulation and emotional intelligence can predict teachers' ability to conduct mindfulness teaching. The research method used is quantitative research with a correlational approach. The number of research samples consisted of 67 inclusive PAUD teachers, selected using a purposive sampling technique, with the criteria that teachers teach in inclusive PAUD and have a minimum of one year of teaching experience. Data analysis using descriptive analysis and multiple regression. The results showed that emotional intelligence and emotion regulation together had a significant effect on Mindful Teaching in Inclusive PAUD teachers. The research findings indicate that 58.3% of the variance in mindful teaching was influenced by emotion regulation and emotional intelligence. Emotion regulation and emotional intelligence play a significant role in predicting mindful teaching. Keywords: mindful teaching, emotion regulation, emotional intelligence, inclusive PAUD